An Opportunity to Be Heard: Family Experiences of Coronial Investigations Into Missing People and Views on Best Practice - Dartnall, Stephanie; Goodman-Delahunty, Jane; Gullifer, Judith (Frontiers in Psychology, 2019)
Experiences of 15 family members and friends of missing people who experienced a coronial investigation into the suspected death of a missing person in New South Wales, Australia were examined via in-depth interviews to explore perceptions of the impact of coronial proceedings on well-being, and views on best practice approaches to families in the Coroner’s Court. Transcripts were thematically analysed, yielding six key themes in participant experiences of inquests: (1) Opportunity to be heard, (2) A chance for education, (3) If you are human with me (sensitive treatment and language), (4) Timely investigations, (5) A public and formal court environment, and (6) Coronial outcomes. Overall, families benefitted from opportunities to have input and feel heard, compassionate treatment, and appropriate education about the process and available support services. A detriment on well-being was described when these factors were precluded. Some participants perceived positive outcomes arising from public awareness of cases of missing people, formalities that conveyed respect, and timeframes that enabled further investigation or preparation for the inquest. Others reported distress and trauma in response to significant delays that led to a loss of evidence, intrusive media and unknown persons in court, and unwelcoming, formal court environments. Some participants were profoundly distressed by a finding of death and by the procedures that followed the inquest, emphasising the need for post-inquest debriefing and ongoing support. These findings deepen our understanding of coronial practices, and of measures to prevent harm, that will be instructive to other coronial jurisdictions. Further research should examine family experiences in contexts where there are variable coronial proceedings or procedures that result in legal findings of death.